Balancing Academic with Research: A Paradox - Lamsal, Madhab (Annals of Clinical Chemistry and Laboratory Medicine, 2016)
The job requirement in many health institutions and professional academic institutions stresses the need to contribute in three main aspects: academics, service and research. While it may have detailed guidelines for the academics and service components, there is no clear workings on the research and ambiguously stresses that one should do quality research and publish a quality findings that may directly benefit the subjects/populations under study. Moreover, it is given undue weightage in job stability and promotions. Paradoxically, no one clearly emphasizes on the quality resources and the time that needs to be allotted for the research activities. Developing a research group at times becomes more challenging and less sustainable. Although much time is demanded to be invested on academics and service aspects, research, where no defined hours and inputs are mentioned, remains a yardstick of professional success and rewards.